EVALUATION OF FLOW FLUCTUATIONS OF SMALL LOW-MOUNTAIN RIVERS OF UZBEKISTAN IN RESPONSE TO POSSIBLE FUTURE CLIMATE CHANGES - N.Z., Sagdeev; T, Khamzaeva J. (International Journal of Psychosocial Rehabilitation, 2020)
the factors which have an impact on the river flow are considered in the article. The opinion of scientists who state that rivers are the product of climate is known. In this regard the changes of atmospheric precipitation, air temperature for different periods of the year and flow of the small low-mountain rivers of Uzbekistan were investigated. The relationships between flow and atmospheric precipitation were derived. Using these relationships and scenarios of possible future climate changes adapted to Central Asian conditions the evaluating flow forecast was made for 14 small low-mountain rivers of Uzbekistan. The analysis of values of maximum flow for small low-mountain rivers in future was fulfilled.